Migration and socio-political orientations of religious and non-religious student youth - Elena A. Kublitskaya (Наука. Культура. Общество, 2023)
Migration processes in the context of the expansion of world economic relations inevitably affect the main spheres of life of the entire world community. The emigration of the most active part of the indigenous population of Russia, predominantly educated and highly professional, is an acute problem, as it inevitably leads to risks to the national and geopolitical security of the state. The growing uncontrolled migration process aimed at the outflow of the mobile indigenous population in the new Russian social reality actualizes the study of the motives of emigrant moods, socio-economic, socio-political orientations, socio-cultural positions, ethno-confessional traditions and customs, spiritual and moral values of youth and, first of all, highly educated part of the younger generation: students. The article analyzes the materials of a sociological study conducted by the Institute for Demographic Research of the Federal Scientific Research Center of the Russian Academy of Sciences in 2022 among students in three constituent entities of the Russian Federation: Moscow, the Republic of Tyva and the Belgorod Region. The focus of the study is aimed at identifying the possible impact of religious and non-religious worldviews on the emigrant orientations of the young part of the Russian population. The set goal was solved with the help of sociological methods of building worldview groups (“religious”/“non-religious”) and typological groups (“settled”/projective “emigrants”). The sociological search was based on a comparative analysis of the assessments and positions of representatives of these groups in relation to religious, national, socio-economic and socio-political problems. The results of a sociological study show that religious ideas and traditions, spiritual and moral values directly related to them play a significant role in the patriotic and civic positions of student youth in relation to Russian society and the state.